(untitled) (Indian Journal of Animal Production and Management, 2013)
This study was planned to investigate the present management condition and to identify the problems related to milk production of private dairy farms of Khanapara area of Guwahati. For about three months, door to door survey was conducted where 150 farm owners were interviewed. From the survey it was reported that about 60% farms belong to landless personal, 14% farms to service personal, 20% farms related to agriculture and 6% farms managed by others. The average number of cow per farm was 20. Almost all cows in the farms were crossbred. Most of the cow shed was constructed by galvanized iron sheet (50%), straw (26%), half building (20%) and only 4% building. Fifty three, thirty four & thirteen farm had closed, semi-closed and open house respectively for their cows with 60% proper ventilation and 40% proper drainage system .Ninety-eight percent farm was used as untreated paddy straw and the rest treated straw for feeding. Seventy percent of farmers do not cultivate fodder crops due to the lack of land and the rest lack of knowledge and awareness etc. The most important constraint of the dairy farming was scarcity of green fodder; good quality concentrates feed, unhygienic production of milk and capital. It is expected that if all these facilities and awareness campaign may be provided to them the very dense milk production area i.e. Khanapara will be improved.